The Evolution of a Mediated Systematic Review Search Service. Issue 1 (2nd January 2022) - Russell, Fiona; Grbin, Lisa; Beard, Frances; Higgins, Julie; Kelly, Blair
ABSTRACT: Librarian contribution to systematic reviews and other evidence summaries is well-documented. Many libraries offer sophisticated support, including mediated search services. Tiered services are beginning to emerge, but few libraries offer fee-for-service models. This paper updates an earlier mediated search pilot delivered by the Health team at Deakin University library. The service has evolved to an expanded multi-tier model with a fee-for-service top tier. The tiers consist of online self-help and consultations through to proof-reading of searches, mediated search design and search translation. This new model was trialled and operationalised during the COVID-19 pandemic in 2020, a time with greater researcher focus on reviews than on field or lab-based research due to lockdown restrictions. This increased demand contributed to service development. The multi-tier model provided opportunity for librarian skill development including peer upskilling and co-authorship. Recognition of librarian contribution is important in mediated searching. The multi-tier service will continue to evolve. There is currently appetite amongst researchers for fee-for-service mediated search. Deakin librarians have also been working with researchers in emerging automation and living reviews and these technologies are likely to impact future directions of the services. Growth in other disciplines may also influence service expansion.